Could the Use of Nitrification Inhibitor Optimize the Nitrogen Use Efficiency of Corn Production? - Pedro Morinigo; Dorivar A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2023)
Nitrogen (N) is an essential nutrient for corn production, higher grain yields are dependent on N fertilizer application. Substances like the nitrification inhibitors (NI) were created to increase yields, promote nitrogen use efficiency (NUE), and reduce N losses. The study was carried out in ten site-years in Kansas from 2017 to 2021, with the objective of evaluating the nitrogen agronomic efficiency (NAE) in corn with and without the use of NI and comparing corn grain yield, grain N uptake, and soil mineral nitrogen content with the use of the NI. Nitrogen fertilizer at the rates of 100, 150, and 200 lb of N/a using anhydrous ammonia (AA) as source was applied to the soil with and without the combination of NI (nitrapyrin) in the spring, also a treatment with 0 lb of N/a without NI was used as control. Soil ammonium average content in V8 growth stage was higher with the use of the NI at the rate of 150 lb of N/a, AONR and EONR values were lower with the use of NI. Higher N grain uptake and NAE were obtained when 150 lb of N/a was applied with NI combination.
Keywords: Nitrification; nitrogen; corn